2012
DOI: 10.3121/cmr.2012.1084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nasal and Nasopharyngeal Swabs for Influenza Detection in Adults

Abstract: Objective: Examine differences in the detection of influenza by specimen and test type using paired nasal and nasopharyngeal swabs. Design: Prospective studySetting: Enrollment took place between January and March 2007 in a central Wisconsin population.Participants: Adult patients were screened and enrolled by trained research coordinators following medical encounters for acute respiratory illnesses of <10 days duration.Methods: Paired nasal and nasopharyngeal swabs were collected from consenting patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 13 publications
2
47
0
1
Order By: Relevance
“…The result of the swab test differs according to the sampling site, e.g. testing on nasal swabs is less sensitive than on nasopharyngeal swabs [29]. We observed one false negative M. pneumoniae PCR result, yet with a positive serology and consistent clinical findings of pneumonia.…”
Section: Discussionmentioning
confidence: 76%
“…The result of the swab test differs according to the sampling site, e.g. testing on nasal swabs is less sensitive than on nasopharyngeal swabs [29]. We observed one false negative M. pneumoniae PCR result, yet with a positive serology and consistent clinical findings of pneumonia.…”
Section: Discussionmentioning
confidence: 76%
“…Sensitivity may have been reduced by time since symptom onset as 26% of clinic samples were collected five or more days after symptom onset when influenza virus is no longer at its highest concentration and as detectable by rRT‐PCR . While nasopharyngeal aspirates or swabs have been considered the best samples for influenza detection in epidemiologic studies, a paired comparison of HCW‐collected nasal and NP swabs for influenza virus detection by PCR in the United States found no significant difference between the two methods although the sensitivity of nasal swabs was lower. Prior studies comparing nasal self‐swabs to HCW‐collected nasal swabs among adults have shown high sensitivity and specificity of nasal self‐swabs .…”
Section: Discussionmentioning
confidence: 99%
“…With this method of detection, specimen processing requires nucleic acid stability rather than organism viability previously needed for culture. Many studies have compared various types of specimens, swabs, and processing buffers for influenza and other respiratory virus RT‐PCR assays [Abu‐Diab et al, ; Hernes et al, ; Irving et al, ; Spackman et al, ]. Laboratory‐based studies have found that influenza RNA was stable on dry swabs for days prior to processing if kept at room temperature or cooler [Moore et al, ; Druce et al, ].…”
Section: Introductionmentioning
confidence: 99%